STRATEGI PEMBERDAYAAN PEREMPUAN DI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KOTA SUNGAI PENUH: NANIK MANDASARI, EKA SEPTIANI - NANIK MANDASARI, S.IP., M.Si (JURNAL ADMINISTRASI NUSANTARA, 2021)
The women's empowerment strategy is one of the government's programs as an effort to solve the problems faced by the community so that it can fulfill the desires and needs of the community towards a better and more advanced direction. The purpose of this study was to determine the process of the Women's Empowerment Strategy in the Office of Women's Empowerment and Child Protection in Sungai Penuh City and the factors that influence it. The type of research used is descriptive qualitative. The data used there are two types of data, namely primary data and secondary data, the data was analyzed descriptively qualitatively which was collected by the author and then displayed in the form of sentences according to interviews from 10 informants. The research uses a phenomenological type. Data collection techniques used instruments in the form of observations, interviews, literature studies and documents. The results showed that there were four related issues, namely: women's participation was good, the programs implemented were not optimal, women's awareness was still lacking, and socialization was not evenly distributed throughout society. The hope in the future is that through the strategy implemented by the Office of Women's Empowerment and Child Protection in Sungai Penuh City regarding the strategy of empowering women, it can be carried out in stages and continuously and guidance for women must continue to be improved.